Metabolomics of Rice Bran Differentially Impacted by Fermentation With Six Probiotics Demonstrates Key Nutrient Changes for Enhancing Gut Health - Seyoum, Yohannes; Humblot, Christèle; Baxter, Bridget A.; Nealon, Nora Jean; Weber, Annika M.; Ryan, Elizabeth P. (Frontiers in Nutrition, 2022)
The consumption of rice bran has been shown to have a positive effect on nutritional status and prevention of chronic diseases related to hundreds of metabolites with bioactivity. Consumption after fermentation can even lead to specific beneficial effects, yet is lacking complete characterization when fermented with diverse strains. The objective of this study was to examine the effect of fermentation on the rice bran metabolite profile. Bacterial probiotics (Bifidobacterium longum, Limosilactobacillus fermentum, Lacticaseibacillus paracasei, Lacticaseibacillus rhamnosus and, Escherichia coli) were used to ferment rice bran alone or after incubation with yeast probiotic Saccharomyces boulardii. Fermented rice bran was methanol extracted and analyzed by UPLC-MS/MS. The metabolome of the two fermentation types was deeply modified when compared with non-fermented rice bran. The two-step fermentation provided alternative substrate to the bacteria in a few cases. Key metabolites of high nutritional value (essential amino acids, vitamins) and gut health (arabinose, maltotriose) were identified.